EVALUATION OF METABOLIC BIOCHEMICAL TESTS, BODY MASS INDEX VALUES AND PERIODONTAL / PERI-IMPLANT CLINICAL PARAMETERS OF PATIENTS REHABILITATED WITH PROSTHETIC DENTAL IMPLANTS OF AT LEAST 1 YEAR - Mihaela Cornelia Doru (Butnaru); Melania Olimpia Cojocaru; Dorin Nicolae Gheorghe; Dora Maria Popescu; Luana Corina Lascu; Carmen Nicolae; Ioana Mitruț; Eugen Stoicănescu; Alex Ioan Sălan; Horia Octavian Manolea (Romanian Society of Oral Rehabilitation, 2023)
The aim of this study was to evaluate the possible correlations between the results of metabolic biochemical tests, the value of body mass index and periodontal / peri-implant clinical parameters in patients in the study group. All patients in the study group (n = 71), attending at least 1 year after implant prosthesis, were investigated and the following anthropometric, clinical and paraclinical parameters were analyzed: height, weight, body mass index, abdominal circumference, blood pressure, blood glucose, periodontal probing depth, bacterial plaque index, total bleeding index on probing, lipid profiling (total cholesterol, triglycerides (TGL), high-density lipoprotein (HDL), LDL). The data obtained after the epidemiological-statistical analysis indicated the existence of the correlations between metabolic biochemical markers and BMI (body mass index), also between abdominal circumference and age as well between bacterial plaque indicators and the presence of the disease in peri-implant tissues. In the case of correlations between metabolic biochemical markers and peri-implant disease as well as dyslipidemia and periodontal disease, no significant association was observed.